Recommendations for optimizing research regarding the effects of dehydration on athletic performance - Francisco, R.; Armstrong, L. E.; Silva, A. M. (Sports Medicine, 2026)
Dehydration`s adverse impact on athletic performance is a critical concern in sports science, yet its investigation remains challenging due to interindividual variability and methodological inconsistencies. Traditional reductionist approaches, which isolate single variables, are insufficient to capture the multifactorial nature of dehydration, which emerges from dynamic interactions among physiological and behavioral factors. These include the method of inducing dehydration, protocol duration, type of fluid loss, environmental conditions, participant characteristics, assessment techniques, and potential nocebo effects. Despite the complexity and relevance of this issue, standardized guidelines for designing sport-specific dehydration studies are lacking. This article addresses this gap by cataloging key interacting variables and offering structured, adaptable guidance rather than proposing a rigid framework. It introduces a dual framework of `challenges and considerations` and `recommendations` for each factor, aiming to support researchers in developing rigorous, context-specific study designs. Ultimately, this approach will promote a more nuanced understanding of dehydration and facilitate reproducible, sport-relevant research advancement.